2023
DOI: 10.3389/fcimb.2023.1232391
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis TmeB antagonizes actin polymerization via direct interference with Arp2/3 activity

Abstract: Chlamydia trachomatis is an obligate intracellular pathogen that actively promotes invasion of epithelial cells. A virulence-associated type III secretion system contributes to chlamydial entry and at least four effectors have been described that are deployed during this time. Two of these invasion-related effectors, the translocated membrane-associated effectors A and B (TmeA and TmeB), are encoded in a bi-cistronic operon. TmeA directly activates host N-WASP to stimulate Arp2/3-dependent actin polymerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…In our study, we sought to define PPIs for all the previously uncharacterized cT3SS effector proteins and included CT695 (TmeB) as at the onset of this study TmeB had no function ascribed to it. Recent work has since shown that ectopically expressed TmeB targets the ARP2/3 complex 71 . While we did not find components of the ARP2/3 complex in our infection AP-MS, we did identify an actin-binding protein, inverted formin 2 (INF2).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we sought to define PPIs for all the previously uncharacterized cT3SS effector proteins and included CT695 (TmeB) as at the onset of this study TmeB had no function ascribed to it. Recent work has since shown that ectopically expressed TmeB targets the ARP2/3 complex 71 . While we did not find components of the ARP2/3 complex in our infection AP-MS, we did identify an actin-binding protein, inverted formin 2 (INF2).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the interaction between N-WASP and SNX9 might explain Dyn2-dependence toward TmeA signaling. Intriguingly, TmeA also bears similarity with the C. pneumonaie secreted effector SemD 49 , 50 , which recruits the BAR-domain proteins PACSIN and SNX9 to induce membrane curvature and promote pathogen engulfment. On this basis, TmeA-mediated Dyn2 regulation could manifest via the formation of SNX9/Dyn2 heterodimers, providing a mechanism of Dyn2 modulation distinct from actin remodeling.…”
Section: Discussionmentioning
confidence: 99%